Effect of Rabbit Manure as Bio-fertilizer on Chilli Pepper Plant (Capsicum annuum) Growth Performance - Azammierah Johari (2018)
Rabbit manure is known as one of better source by-products to make bio-fertilizer. However in previous years, rabbit manure bio-fertilizer is rarely being used by farmers due to low rabbit production in Malaysia. To date, rabbit farming has become one of the expand industry in Malaysia to fulfil demand of meat sources. Continuously, it will leads to increment of rabbit manure production. The aim of the study was to investigate the effects of rabbit manure bio-fertilizer on chilli pepper plant growth performance. The effectiveness of rabbit manure bio-fertilizer was compared to commercial bio-fertilizer based on chilli pepper plant height, number of leaf, average size of leaf and number of chilli pepper produced. The foliars were sprayed on chilli pepper plants twice a week respectively. The findings showed rabbit manure bio-fertilizer was less effective compared to commercial bio-fertilizer due to low availability of nutrient content such as nitrogen and phosphorus to boost the plant growth. Statistically, commercial bio-fertilizer showed significant effects (p<0.05) on plant height where at the end of planting period, control plants achieved 41.20 ± 9.56 cm height while plants applied with rabbit manure bio-fertilizer only reached 11.77 ± 0.63 cm height. Nevertheless, flowering and fruits only appeared on plants applied with commercial bio-fertilizer. The output of this study can be used to identify potential bio-fertilizer that may promote growth performance of chilli pepper plant as well as to reduce the use of chemical fertilizer in the nursery. Other than that, it also encourage better waste management in rabbit farming.